(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate cerebral perfusion characteristics using arterial spin labeling (ASL) MRI and evaluate the association between regional cerebral blood flow (CBF) and cognitive impairment in patients with dementia. Methods: A cross-sectional study was conducted on 20 patients diagnosed with dementia according to DSM-5 criteria at the National Geriatric Hospital. Cognitive function was assessed using the Mini-Mental State Examination (MMSE). CBF values were measured using ASL MRI at the parietal lobe, temporal lobe, hippocampus, and cingulate gyrus. Spearman correlation analysis was used to evaluate the relationship between CBF and MMSE scores. Results: The lowest mean CBF was observed in the parietal lobe (44.58 ± 3.96 ml/100g/min), while the highest was found in the cingulate gyrus (55.83 ± 7.40 ml/100g/min), with a statistically significant difference (p < 0.001). Moderate positive correlations were found between MMSE scores and CBF in the parietal lobe (r = 0.561, p = 0.010) and hippocampus (r = 0.548, p = 0.012). No significant correlations were observed in the temporal lobe or cingulate gyrus. Conclusion: ASL MRI is a non-invasive technique with potential value in assessing cerebral perfusion in dementia. Reduced CBF in the parietal lobe and hippocampus is associated with cognitive decline, suggesting its potential role in clinical evaluation.